Association Between Promoter Methylation of Vitamin D Metabolic Pathway Genes and Tuberculosis and Diabetes Comorbidity in a Chinese Han Population: A Case–Control Study - Chen Y; Peng AZ; Li K; Liu L; Zhang F; Chen J; Zhang H; Li L; Yang H; Xu X; Zhang Q (Dove Medical Press, 2022)
Yong Chen,1,* An-Zhou Peng,2,* Kun Li,3 Lei Liu,1 Fazhen Zhang,2 Jin Chen,2 Huifen Zhang,2 Linyang Li,2 Hailin Yang,4 Xihai Xu,3 Qiu Zhang1 1Department of Endocrinology, First Affiliated Hospital of Anhui Medical, University, Hefei, 230022, People's Republic of China; 2Department of the Fifth Tuberculosis, Chongqing Public Health Medical Center, Chongqing, 400030, People's Republic of China; 3Department of Health Management Center, First Affiliated Hospital of Anhui Medical University, Hefei, 230022, People's Republic of China; 4Department of Infection, the People's Hospital of Shizhu, Chongqing, 400000, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiu Zhang, Department of Endocrinology, First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People's Republic of China, Email zhangqiu@ahmu.edu.cn Xihai Xu, Department of Health Management Center, First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People's Republic of China, Email 2xhai@163.comBackground: Deficiency vitamin D and hyperglycemia could be related to weakened innate immune response and aggravate the progression of tuberculosis (TB). This study hypothesized that DNA promoter methylation of the pivotal genes in the vitamin D metabolic pathway might be related to diabetes and tuberculosis co-morbidity (TB-DM) susceptibility.Methods: A total of 50 TB-DM and 50 healthy subjects (HS) were included in the present study. Targeted bisulfite sequencing was applied to detect the methylation of the promoter regions of candidate genes in the vitamin D metabolic pathway (CYP24A1, CYP27B1, CYP2R1, DHCR7, and VDR) in whole blood.Results: The overall methylation level of candidate genes in this study was lower in patients with TB-DM than HS, except for CYP2R1. The results of the ROC demonstrated the potential of CYP24A1, CYP27B1, DHCR7, and VDR promoter methylation as a biomarker for diagnosing TB-DM, with all the AUC above 0.7. In subgroup analysis, we found that lower circulating vitamin D is related to a low level of CYP24A1, CYP27B1, and DHCR7 promoter methylation in patients with TB-DM. With decreasing methylation level, risk of TB-DM was significantly decreased (odds ratio, 95% CI 0.343, 0.144- 0.821 for CYP24A1; 0.461, 0.275- 0.773 for CYP27B1; 0.09, 0.015- 0.530 for DHCR7; 0.006, 0.0003- 0.115 for VDR). Besides, our results revealed that there was a significant correlation between DNA promoter methylation of selected genes in the vitamin D metabolic pathway and platelet indices in TB-DM. However, there was no correlation between DNA methylation of the four genes and fasting glucose and HbA1c.Conclusion: Our results could suggest that the selected genes in the vitamin D metabolic pathway may be involved in the pathological process of TB-DM, but independent of the process of hyperglycemia to impaired immune responses to Mtb.Keywords: tuberculosis, diabetes, epigenetics, DNA methylation, vitamin D